The beneficial effects of taurine in preventing metabolic syndrome. Issue 4 (26th February 2016) - Chen, Wen; Guo, Junxia; Zhang, Yanzhen; Zhang, Jing
Abstract : A review of the data from in vitro, animal and limited human studies of the beneficial effects of taurine on obesity, dyslipidaemia, diabetes mellitus and hypertension, as well as the possible metabolic and molecular mechanisms for the prevention of metabolic syndrome by taurine. Abstract : Metabolic syndrome, a cluster of risk factors for diabetes and cardiovascular disease, has become a very serious public health concern. A number of studies have provided evidence that taurine has an efficient action against metabolic syndrome, which includes reducing triglycerides to prevent obesity, improving insulin resistance to regulate glucose metabolism, lowering cholesterol (especially decreasing VLDL + LDL cholesterol and increasing HDL cholesterol) to prevent diet-induced hypercholesterolemia, and regulating the renin-angiotensin-aldosterone system and the kallikrein-kinin system etc. to reduce blood pressure. This review summarizes the data from in vitro, animal and limited human studies of beneficial effects of taurine on obesity, dyslipidaemia, diabetes mellitus and hypertension, and addresses the possible metabolic and molecular mechanisms of the prevention of metabolic syndrome by taurine.